Energy Efficiency and Cost-effectiveness Analysis on Flare Gas Recovery Consumption Sources at Industrial Gas Processing Plant - Enayati, Mahdi; Sayed Mohsen Hosseini; Parvizian, Fahime (Journal of petroleum science and technology, 2024)
Flared gas recovery (FGR) plays a crucial role in controlling greenhouse-gas emissions and improving energy-efficiency in industrial gas plants. Every year, significant amounts of valuable gases are lost through flaring, leading to both environmental/economic consequences. Moreover, developing an effective and cost-efficient strategy for flare gas recovery remains a major challenge, requiring a careful balance between technical feasibility and financial viability. This study introduces a new approach to flare gas recovery by investigating two alternative utilization scenarios in a large-scale gas refinery. Furthermore, unlike conventional studies focusing primarily on economic feasibility, this research comprehensively integrates exergy analysis to evaluate energy and financial performance. This study analyzes all potential consumption sources of recovered flare gas and evaluates the feasibility and efficiency of two major effective scenarios. In the first scenario, recovered flare gases are compressed to 70 bar and injected into the gas sweetening unit, achieving an exergy-efficiency of over 69%. In the second scenario, recovered gases are redirected to existing compressors in the gas condensate stabilization unit, yielding a calculated exergy efficiency exceeding 78%. A detailed economic evaluation, considering both capital and operating expenditures, reveals that the overall flare gas recovery system has a return on investment of 17 months. Scenario one requires 24 months to break even, whereas scenario two achieves profitability in just 11 months. Ultimately, findings demonstrate that directing recovered flare gases to compressors of gas condensate stabilization unit provides most efficient and optimal utilization of these gases. Also, this research presents a viable solution for reducing emissions, minimizing waste, and maximizing both energy and financial resources in gas processing plants.